2020
DOI: 10.1186/s12889-020-09481-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an influenza information pamphlet on vaccination uptake among Polish pupils in Edinburgh, Scotland and the role of social media in parental decision making

Abstract: Background In Edinburgh, Scotland, lower influenza vaccine uptake has been observed in primary school children in the Polish community. Methods To address this disparity, the Polish-language version of the NHS Health Scotland influenza information pamphlet was updated and distributed in 2018 to all identified Polish pupils attending three pilot schools. The impact of the revised pamphlet was evaluated by examining changes in vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…43 studies 8 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 addressed barriers to or facilitators of vaccine uptake. Access and acceptance were the most common themes, with awareness, affordability, and activation reported to a lesser extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 studies 8 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 addressed barriers to or facilitators of vaccine uptake. Access and acceptance were the most common themes, with awareness, affordability, and activation reported to a lesser extent.…”
Section: Resultsmentioning
confidence: 99%
“… 38 , 55 In the absence of translated or accessible information, migrants also turned to alternative and unregulated sources, such as Google, social media, friends, and family. 25 , 36 , 56 , 59 , 60 …”
Section: Resultsmentioning
confidence: 99%
“…Another study in the United Kingdom reported a slightly similar pattern in crude vaccine uptake across different years among Jewish and Muslim people [ 112 ]. Among minority and religious groups in general, including ethnic minorities, Roma, Jewish and Arab communities had lower vaccination coverage rates compared to the general (local) population [ 42 , 54 , 69 , 70 , 72 , 76 , 86 , 90 , 101 , 109 ]. Vaccination coverage by disadvantaged areas revealed significant variation and association between level of deprivation and uptake.…”
Section: Resultsmentioning
confidence: 99%
“…(35,52) In the absence of translated or accessible information, many migrants reported that they turned to alternative and unregulated sources, such as Google, social media, friends, and family. (22,33,53,56,57) ii. Practical and legal barriers to accessing healthcare and services Practical and legal barriers to accessing healthcare (whether perceived or real) and vaccination delivery models, meant that many migrants experienced exclusion and challenges accessing vaccination services.…”
Section: Barriers and Facilitators To Vaccine Uptake In Migrant Populationsmentioning
confidence: 99%